Mereduksi Perilaku Menyontek Siswa di Era “Merdeka Belajar” Melalui Layanan Bimbingan Kelompok - Mia Cahyani Putri; Dosi Juliawati; Ainil Khuryati; Hengki Yandri (Jurnal Penelitian Bimbingan dan Konseling, 2020)
In this "Merdeka Belajar" era, education is a means for students to be able to glorify themselves by displaying good behavior and character. However, not all students in receiving education show commendable behavior as there are still students who make assignments and examinations by cheating. So the purpose of this study is to reduce student cheating behavior through group counseling services. This research method is a type of experiment and uses one group pre-test post-test design with the study population that is the State Junior High School 4 Kerinci students and sampling is done by purposive sampling totaling 10 people. The research data was revealed using a cheating behavior scale that was compiled by the researcher himself and had been tested for validity and reliability with Alpha Cronbach's value 0.832. Further data has been collected in the analysis using the wilcoxon Signed Ranks test. The results of this study revealed that there were significant differences in cheating behavior among students before and after group counseling services were provided. This means that students' cheating behavior is reduced after group counseling services are provided.Keyword:  cheating; merdeka belajar; Group Counseling